The death and life of shopping malls: an empirical investigation on the dead malls in Greater Lisbon. Issue 4 (8th August 2017) - Ferreira, Daniela; Paiva, Daniel
Abstract: At a moment when new retail formats are emerging and consumers are changing their preferences, it is vital to reflect on the existing shopping malls, which are being challenged in European cities. With their vitality endangered, many become dead malls, a phenomenon that has increased over recent years. With this in mind, the objective of this study is to explain the factors behind the proliferation of dead malls through an empirical analysis of the evolution of shopping malls in Greater Lisbon, Portugal. We combine three sets of retail change theories (cyclic, conflict and environmental) with current perspectives on the resilience of urban retail. We expect that our study will contribute toward current debates on the resilience of shopping malls. The methodology of our study comprises two stages. First, we updated the Greater Lisbon shopping mall database and analysed the growth and decline of each shopping mall type over the last 44 years. In a second phase, we conducted a fieldwork survey on 150 shopping malls, which allowed us to identify and profile the dead malls of Greater Lisbon. Our results show that dead malls match declining shopping mall types, and we discuss four factors affecting the resilience of shopping malls.